Capacidade funcional, estresse percebido e qualidade de vida relacionada à saúde de pessoas com sequelas de acidente vascular encefálico - Silva, Cleane Rosa Ribeiro da (2019)
The repercussions of the CVA bring unexpected challenges to the lives of survivors, sucg as functional limitations, which can lead to stressful situations and reflect negatively on the HRQOL of this population. Objective: To evaluate the functional capacity, the perceived stress and HRQOL of people with sequels of CVA. Method: Cross-sectional, exploratory and descriptive study, with a quantitative approach, carried out with 160 people with sequels of CVA registered in Family Health Units of the city of João Pessoa-PB, from July to November 2018. The data were collected using a semistructured instrument to obtain demographic and health data, the Barthel Index, the Perceived Stress Scale and the Specific Quality of Life Scale for CVA. Data analysis used descriptive and inferential statistics. The project was approved under number 2.994.882, with opinion CAAE 91360718.1.0000.5188. Results: Participants presented moderate functional dependency, with statistical significance between the age group (p=0,039), the source of income (p=0,004), physical activity (p=0,004), self-reported health status (p<0,001), motor change (p=0,049), muscle weakness (p=0,011) and caregiver (p<0,001). Perceived stress has been identified, relating statistically with the muscle weakness (p=0,041), mood disorder (p=0,032) and caregiver (p=0,017). It was low HRQOL, with greater commitment in the areas of social roles and family Roles. The HRQOL presented statistically significant difference with physical activity (p<0,001), the time of the last bird (p<0,001), the motor change (p<0,001), muscle weakness (p=0,025), mood disorder (p=0,008) and caregiver (p<0,001). There was a statistically significant correlation between the HRQOL with functional capacity (r=705; p<0,001) and perceived stress (r=-436; p<0,001), demonstrating that the HRQOL of people with CVA sequels rises, as the functionality increases and stress decreases. Conclusions: The functional capacity and the perceived stress relate significantly to the HRQOL of people with sequels.